Analisis Pengaruh Debt to Equity Ratio (DER), Return on Equity (ROE) dan Nilai Perusahaan Terhadap Return Saham pada Subsektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Abd Halim; Ermaini Ermaini; Ari Setiawan (Universitas Batanghari, 2022)
This study aims to provide empirical evidence regarding the effect of debt to equity ratio (DER), return on equity (ROE) and Company Value on Stock returns. The population in this study is a Property and Real Estate Subsector company listed on the Indonesia Stock Exchange (IDX) for the period 2015-2019. The sampling technique uses purposive sampling which results in 30 companies to be used as samples. The type of data used is secondary data in the form of the company's annual financial statements obtained from the Indonesia Stock Exchange (IDX). The data analysis techniques used are descriptive statistics and multiple linear regression analysis. The results of the hypothesis test showed that the debt to equity ratio (DER), return on equity (ROE) and the value of the company simultaneously affected the return of the stock. Partially only the Value of the Company affects the return of the stock.